Effects of Task Complexity and Planning Conditions on L2 Argumentative Writing Production. Issue 8 (17th November 2018) - Rahimi, Muhammad; Zhang, Lawrence Jun
ABSTRACT: Investigating the effects of task design and implementation features on second language (L2) production is necessary, as the findings can provide potential insights into pedagogical and assessment task design and sequencing as well as into the nature of L2 learners' attentional resources. To this end, this study probed into the effects of task complexity and pretask planning on L2 writing production. Eighty L2 learners of upper-intermediate English proficiency were invited to complete two writing tasks of varying degrees of complexity in relation to the reasoning demands and the number of elements under pretask versus no pretask planning conditions. Results show that as a function of increasing task complexity, one dimension of the syntactic and lexical complexity, content, organization, and writing quality improved, whereas accuracy and fluency reduced. Providing 10 minutes pretask planning had significant favorable effects on one dimension of syntactic complexity and fluency, no effects on accuracy or lexical complexity, and significant positive impacts on the content, organization, and writing quality. These findings lend partial support to the Cognition Hypothesis, the Trade-off Hypothesis, and attentional funneling in L2 writing. Theoretical, methodological, and pedagogical implications of the study for task design and implementation as well as for task-based assessment in language education programs are discussed.